PENERAPAN PEMBELAJARAN BERBASIS INKUIRI DALAM UPAYA MENINGKATKAN PEMAHAMAN MATA PELAJARAN PENDIDIKAN AGAMA HINDU DI SMAN 1 BANGLI TAHUN AJARAN 2021/2022 - Gede Mertha Adiyasa; I Nengah Juliawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Application of Inquiry-Based Learning in an Effort to Improve Understanding of Hindu Religious Education Lessons for Class XI Social Sciences 1 Semester II SMAN 1 Bangli Academic Year 2021/2022. The purpose of this study was to describe the learning process through the implementation of inquiry-based learning for Class XI IPS 1 SMAN 1 Bangli students, to find out to what extent the implementation of inquiry-based learning could improve students' understanding of Class XI IPS 1 SMAN 1 Bangli on Hindu religious education subjects and manners. , to find out to what extent the implementation of inquiry-based learning can increase the creativity of Class XI IPS 1 students of SMAN 1 Bangli and to determine student responses to the implementation of inquiry-based learning of Class XI IPS 1 students of SMAN 1 Kintamani. This research is a classroom action research involving 33 students of Class XI IPS 1 Semester II SMAN 1 Bangli. Some of the variables investigated in this study are as follows (1) the results of creativity, and (2) students' understanding in learning Hindu religious education, especially morals & sad atatayi. This research procedure will be carried out through 2 (two) cycles, each cycle is carried out for 2 x 40 minutes. Student responses to the implementation of inquiry-based learning for Class XI IPS 1SMAN 1 Bangli students were positive, namely the number of students who responded positively as much as 71.42% and responded negatively as much as 13.57%.